Empirical Evidence on the Reliability of Lateral Supramalleolar Flap over Reverse Sural Flap for Local Soft Tissue Coverage of Dorsum of the Foot and Ankle Defects - Jaiswal, Krishndhari Shankar; Gupta, Samarth; Goil, Pradeep; Mohammad, Arbab; Gupta, Prateek (Indian Journal of Plastic Surgery, 2023)
Background Soft tissue coverage of the distal foot and ankle region has been an area of debate due to the paucity of local flap options. To provide empirical evidence on the reliability of an underreported local alternative for foot and ankle defects, we aim to compare the lateral supramalleolar flap (LSMF) to the reverse sural flap (RSF).Methods During 2016–2019, 48 patients were divided randomly into two equal groups, LSMF and RSF groups respectively. The patients' demographic, surgical, and clinical outcome details were recorded and analyzed.Results Flap necrosis was found in five patients in the group treated with RSF and none in the LSMF group. The mean total number of stages in RSF group was significantly higher than in LSMF group (p < 0.05). The mean operative time for patients in LSMF group was 85.8 ± 18.5 and 54.2 ± 11.2 in RSF group (p < 0.05). Five patients in the RSF group needed additional procedures following flap complications. Nine patients in the LSMF group reported satisfaction outcomes to be “excellent,” five patients reported “good” whereas, in the RSF group, 14 patients reported “excellent,” 5 reported “good,” 3 reported “fair,” and 2 reported “poor” outcomes. Compared to the RSF (46.4 ± 4.3) group, the LSMF group had significantly better foot function indices (34.03 ± 3.9).Conclusion The lateral supramalleolar flap for foot and ankle defects offers better results, reduced complications as well a lesser number of stages and secondary procedures over the traditionally used reverse sural flap.
Keywords: foot defects; lateral supramalleolar flap; reverse sural flap; distal leg; fasciocutaneous flap